HUBUNGAN PERKEMBANGAN ANAK PRASEKOLAH DENGANG STATUS PEKERJAAN IBU - Siti " Nadzirah; Ganis " Indriati; Sofiana " Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract The development of a child is all change that happend in the child, we can see from many as fect such as, motoric, emotional, cognitive and psichologycal aspect. The devolopment of child when the child still student in motoric develop like sensitive motoric and coarse motoric, the development of language and the development of attitude. The aims of the research to indentivity coreletion between development of preschool children and mother’s employment status. The research’s desain used cross sectional. The research had been done in TK pembima 1 Pekanbaru with 98 respondents, that taken by stratified random sampling. The instrument used denver development screening test (DDST). Data analysis used chi square test. Most characteristic of redpondents are 3-6 years (54.1 %), the most of respondents are 44  (44.9 %),  mother employment status is not worked 52 (52.1 %). And  children’s development  are suspect 50 (51,0%). Analysis bivariate to determine relation between development of children’s preschool and mother employment status, variables was analyzed by chi-square test. The results showed  that there was not relation between development of children’s preschool and mother employment status (p value > α). This research recommends to parents to provide a quality time for childrens, so the  children will having growth and development optimally.  Keywords     : children’s preschool, development, mother employment status